Selenium‐binding protein 1 alters energy metabolism in prostate cancer cells. Issue 12 (8th June 2020) - Elhodaky, Mostafa; Hong, Lenny K.; Kadkol, Shrinidhi; Diamond, Alan M.
Abstract: Objective: The broad goal of the research described in this study was to investigate the contributions of selenium‐binding protein 1 (SBP1) loss in prostate cancer development and outcome. Methods: SBP1 levels were altered in prostate cancer cell lines and the consequences on oxygen consumption, expression of proteins associated with energy metabolism, and cellular transformation and migration were investigated. The effects of exposing cells to the SBP1 reaction products, H2 O2 and H2 S were also assessed. In silico analyses identified potential HNF4α binding sites within the SBP1 promoter region and this was investigated using an inhibitor specific for that transcription factor. Results: Using in silico analyses, it was determined that the promoter region of SBP1 contains putative binding sites for the HNF4α transcription factor. The potential for HNF4α to regulate SBP1 expression was supported by data indicating that HNF4α inhibition resulted in a dose‐response increase in the levels of SBP1 messenger RNA and protein, identifying HNF4α as a novel negative regulator of SBP1 expression in prostate cancer cells. The consequences of altering the levels of SBP1 were investigated by ectopically expressing SBP1 in PC‐3 prostate cancer cells, where SBP1 expression attenuated anchorage‐independent cellular growth and migration in culture, both properties associated with transformation. SBP1 overexpression reduced oxygen consumption in these cells and increased the activation of AMP‐activated protein kinase (AMPK), a major regulator of energy homeostasis. In addition, the reaction products of SBP1, H2 O2, and H2 S also activated AMPK. Conclusions: Based on the obtained data, it is hypothesized that SBP1 negatively regulates oxidative phosphorylation (OXPHOS) in the healthy prostate cells by the production of H2 O2 and H2 S and consequential activation of AMPK. The reduction of SBP1 levels in prostate cancer can occur due to increased binding of HNF4α, acting as a transcriptional inhibitor to the SBP1 promoter. Consequently, there is a reduction in H2 O2 and H2 S‐mediated signaling, inhibition of AMPK, and stimulation of OXPHOS and building blocks of biomolecules needed for tumor growth and progression. Other effects of SBP1 loss in tumor cells remain to be discovered.